"Because Modern People Believe in New Skydaddy": Shifting Buddhist Identities and Authorities on Reddit (Aura: Journal for the Study of New Religions, 2023)
Online religion may challenge traditional forms of practice, ideas, values, hierarchies, and authorities. This article explores some of the complex ways in which Buddhism is practiced as a lived religion on the internet. It looks at three case studies from the subreddit /r/Buddhism on Reddit.com and uses these examples as springboards for a broader discussion of Buddhist identity, authority, and authenticityin the twenty-first century. The article also discusses recent relevant scholarship and suggests that Reddit is a valuable yet understudied source of insight into the lives of ordinary religious practitioners in the twenty-first century. The article in particular highlights how Reddit can be a source of insight into “the broad variety of articulations of religious identities, such as the stories of women, gay peopleand other groups whose voices have been marginalized in religious communities throughout history” (Lövheim 2012: 163).